(untitled) (European Journal of Pure and Applied Mathematics, 2013)
Necessary and sufficient conditions for a prime ideal to be a minimal prime ideal and prime ideal to be a principal ideal in an ADL are furnished. And some properties of the special subsets of the set of all prime ideals in an ADL are studied.Â